School Culture to Build Environmental Awareness in SD N Krebet before and during the Pandemic Season - Murniningsih Murniningsih; Rully Widyanti Eka Putri (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2021)
Caring for the environment is one of the visions of SD N Krebet Pajangan Kulon Progo. In the pandemic season, the school culture has experienced very significant changes in the learning process and other school activities. The purpose of this study is to describe how to build environmental awareness of Pre and during the Pandemic Season in SD N Krebet. This study uses an approach qualitative which is included in the intricic case research class with descriptive analysis. The data collection technique is carried out namely observation to determine conditions updates, documentation, and interviews with informants to get data about the conditions of learning and culture school before and during pandemic season. Based on the results of the study, it can be concluded that the implementation of school culture that supports the realization of a vision of environmental awareness is very different in its management both pre and during a pandemic. The management of school culture is seen from the aspects of program planning, implementation and evaluation. When pre-pendemic management to build environmental awareness is carried out more varied, whereas during a pandemic, the management of school culture tends to emphasize knowledge and advice only, but there are some life skills that are taught, namely making masks and using used items as soap containers to wash hands.